Relationship Between Nurse Therapeutic Communication With Respondent Characteristics And Inpatient Satisfaction Level - Nurhanifah, Dewi (Sean Institute, 2022)
Many people feel dissatisfied and think that communication by nurses is still not optimal. The results of a preliminary study at the Banjarmasin Health Center found that four patients said they were satisfied, and nine said they were not satisfied with the services they received, one of which was the lack of therapeutic communication from nurses. This study aims to determine the relationship between nurses' therapeutic communication and respondents' characteristics with the satisfaction level of inpatients at the Banjarmasin Health Center. This type of research is analytic cross-sectional. A total of 50 respondents were taken by purposive sampling. The research instrument used a questionnaire sheet—a bivariate test using Spearman's rank and linear regression multivariate. Univariate analysis obtained that most of the nurses' therapeutic communication was quite good (80.0%), patient satisfaction was quite satisfied (52.0%), the respondent's age was 20-30 years (32.0%), female gender (66.0%), elementary school education (40.0%), other work (60.0%). Bivariate analysis of therapeutic communication with levels of satisfaction (p = 0.466), gender (p = 0.414), education (p = 0.657), and occupation (p = 0.33). The results of the linear regression test were obtained (p = 0.290). There is no relationship between the nurse's therapeutic communication and the characteristics of the respondents with the satisfaction level of inpatients at the Banjarmasin Health Center. Therefore, it is necessary to hold special training for nurses related to therapeutic communication and other training to create patient satisfaction.